EFFORTS FOR THE ESTABLISHMENT OF AKHLAK THROUGH TASAWUF APPROACH IN THE COMMUNITY OF NTORI, BIMA DISTRICT - Abdullah Thalib (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
This article is the result of a descriptive qualitative study on the thinking of a community leader in Ntori Village, Bima Regency named H. Usman Mustakim. Appointed as an appreciation for his dedication to the formation of morals in society as a reflection of a complete human being who is not only knowledgeable but also has to have morals. This research uses the Sufism approach, with the data collection method of observation, interviews, and documentation. The data analysis process includes data collection, data verification, and validation, and concluding. The results of this study are a series of efforts by H. Usman Mustakim to form community morals by providing an understanding of the concept of morality in the style of the prophet and should be able to integrate the personalities of the prophet Sulaiman A.S, the prophet Daud A.S, the prophet Yusuf A.S, and the prophet Muhammad Saw. The four prophets are a reflection of the personal ideal as a servant of Allah, encompassing intelligence, assertiveness and strength, beauty and gentleness, and nobility like the prophet Muhammad.